(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article explores modern methodologies for teaching foreign languages in preschool and school education. It examines communicative, immersive, and technology-driven approaches that enhance language acquisition and learning effectiveness. The study also provides an analysis of best practices and offers recommendations for improving foreign language instruction among young learners.